Evidence-Based Practice in Juvenile Justice - Greenwood, Peter. author. aut Link
IX, 118 p. 12 illus.
Keywords: Over the past 15 years, evidence-based practice in juvenile justice has moved from a concept to a full blown practice in a number of states. They have used research based principles and programs to: - completely reorganize their system for treating juveniles -reduce crime and recidivism -and saved money in the process. Evidence-Based Practice in Juvenile Justice describes the major players in this transformative process, the particular role they play in moving research to practice, and provides recommendations for applying this research in other locations. It will be of key interest to researchers in Criminology and Criminal Justice with a focus on Juvenile Justice or Juvenile Delinquency, or related fields such as Public Policy and Social Work, as well as policy-makers, and practitioners working in the juvenile justice system. .